1990
DOI: 10.1177/000331979004101107
|View full text |Cite
|
Sign up to set email alerts
|

Patency Rate of Implantable Devices During Long-Term Intraaterial Chemotherapy

Abstract: Intraarterial implantable drug delivery systems have been considered as an alternative method for treating patients with unresectable liver malignancies. However, catheter problems with external implanted devices have resulted in limited application of chemotherapy. The introduction of subcutaneous devices offers an opportunity for long-term locoregional chemotherapy. Twelve external intraarterial catheters were implanted into 12 patients and 52 subcutaneously placed devices into 51 patients, all with various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Yamagami et al [21] reported in their study of port-catheter implantation with catheter tip fixation in 128 subjects that the mean number of micro-coils used for catheter tip fixation was 4.6 and that in 93% of these procedures the addition of NBCA-Lipiodol was necessary to obtain sufficient fixation. The present study showed similar results in those cases that did not receive Micronester coils for catheter tip fixation; the mean number of used micro-coils was 4.2 (range, [1][2][3][4][5][6][7][8][9][10][11][12], and in 86% NBCA-Lipiodol was required for sufficient fixation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Yamagami et al [21] reported in their study of port-catheter implantation with catheter tip fixation in 128 subjects that the mean number of micro-coils used for catheter tip fixation was 4.6 and that in 93% of these procedures the addition of NBCA-Lipiodol was necessary to obtain sufficient fixation. The present study showed similar results in those cases that did not receive Micronester coils for catheter tip fixation; the mean number of used micro-coils was 4.2 (range, [1][2][3][4][5][6][7][8][9][10][11][12], and in 86% NBCA-Lipiodol was required for sufficient fixation.…”
Section: Discussionsupporting
confidence: 78%
“…In the past, such catheter placement was done by surgical laparotomy under general anesthesia [3][4][5][6], making this an invasive procedure. However, recent advancements in interventional radiological techniques allow the less invasive implantation of port-catheter systems, that is, percutaneous implantation under local anesthesia [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…anesthesia [5,6,15]; however, the recent development of interventional techniques has made it possible to implant port-catheter systems percutaneously under local anesthesia [3,4,7,8,9,10,11,12,13,14,16,17]. Thus, attention has come to be paid to hepatic arterial infusion chemotherapy which can be performed repeatedly at the outpatient clinic via a percutaneously implanted portcatheter system for patients with advanced liver cancer as one effective treatment from the point of view of prolonging normal-quality survival [2].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, such catheters were placed by surgical laparotomy with the patient under general anesthesia [3][4][5][6], making this procedure invasive. However, recent advancements in interventional techniques allow the implantation of port-catheter systems percutaneously with the patient under local anesthesia [7][8][9][10][11][12][13][14].…”
Section: Objectivementioning
confidence: 99%